PERILAKU PEMILIH TERHADAP KEMENANGAN JOE BIDEN PADA PEMILIHAN UMUM PRESIDEN AMERIKA SERIKAT TAHUN 2020 (Jurnal Nawala Politika, 2023)
The study analyzed voter behavior in the 2020 United States presidential election and the factors influencing the shift in voter preferences in Joe Biden's favor. This study uses qualitative and exploratory research methods to understand the phenomenon of voter behavior in a natural social context. The results showed that there was a significant shift in voter preferences in the 2020 US presidential election. Some of the factors influencing this shift include changing attitudes and views towards candidates, relevant campaign issues, anti-Trump sentiment, perceptions of COVID-19 handling, racial and social issues, and high voter participation. In addition, this study also analyzes the theory of voter behavior in the context of the 2020 US presidential election. Sociological approaches, psychological approaches, and rational choice approaches (economic voting) are used to explain voter behavior in choosing candidates. This approach helps understand how factors such as party identification, perceptions of candidates, and rational considerations influence voter behavior. In conclusion, the 2020 United States presidential election was influenced by various factors including social context, political ideology, sentiment towards candidates, campaign issues, handling of the pandemic, racial and social issues, and voter participation. A deeper understanding of voter behavior and the factors that influence it can help analyze presidential elections and democratic processes in the United States.